Effects of electrode materials and potential gradient on electro-osmotic consolidation for marine clayey soils - Jin, Haihui; Zhang, Lei; Wang, Binghui; Fang, Chen; Wang, Liyan (Frontiers in Earth Science, 2024)
This study conducted experimental investigations into the effects of electrode material and potential gradient on the effectiveness of electro-osmotic consolidation (EO) in strengthening soft soils. Seven laboratory tests were conducted on high-water-content marine clayey soils through EO. In these experimental tests, four different types of electrodes made of steel, copper, aluminum, and composite carbon fiber (CCF) were employed in four tests each to evaluate the consolidation effectiveness.Additionally, four tests, one was the comparitive study for different eletrode materials, were carried out to determine the optimal gradient for the EO using CCF electrode. Several critical properties of the tested soils were examined and evaluated in this study, including the effective voltage utilization, potential distribution, water discharge, discharge rate, energy consumption, and soil bearing capacity. The test results indicated that the CCF electrode had superior performance in water discharge, discharge rate, and average soil water content compared to metal electrodes. Furthermore, CCF led to uniform enhancement of soil strength, with treated soil bearing capacities 6.3 to 12 times higher than initial values, and 1.9 to 2.5 times higher than those attained with metal electrodes. Additionally, an effective potential gradient of 1 V/cm was identified for the EO with the CCF electrode, providing a higher discharge rate and a larger soil strength in a uniform distribution. Moreover, the use of CCF electrode significantly reduced corrosion compared to metal electrodes during the consolidation process, further contributing to improved consolidation efficiency. This study offers valuable insights and recommendations for the utilization of CCF in marine clayey soils, effectively addressing the challenges posed by electrode corrosion and high energy consumption in EO applications.